Identidade de lugar de moradores de Porto de Sauípe-Ba em face da intervenção turística na subjetividade social - Sasaki, Karen Michelly Moraes e (2009)
The present thesis intended to investigate how the identity of place from Porto de Sauipe inhabitants is configured since the intervention of the tourism activity in this area. Some theorists of human and social sciences were invited to support the theory argumentation. The methodological path used was the qualitative methodology, based on the Subjectivity Theory principles. To engender information, there had been open interviews with local residents; there were applied phrases complements, as well as it was required the subjectivity expression throughout mental maps draws. There had been visits to Porto de Sauipe during a six months period uninterruptedly in order to put the instruments into practice. From the field research on, it was possible to testify that the inhabitants identity of place is based on five subjective configurations that were didactically divided into: 1) strong affective relation with the place and inhabitants; 2) political disregard feeling; 3) involvement with touristy dimension; 4) social weirdness feeling; and 5) consciousness about environment care and interaction. Each subjective configuration points out the individual and social needs of the community from Porto de Sauipe, as well as it indicates the need of negative social and environmental impacts reversion showed by residents, since it has an effective participation of the community and the public force on administration, planning and regional development actions.